Geometry Pop-Up Book Learning Media in Increasing Understanding of the Concept of Building Space in Students - Aulia Eka, Aisyah; Avita, Dwi; Wahyudi (Universitas Pendidikan Ganesha, 2023)
Media use in the learning process helps teaching and learning activities. Using media in the learning process makes it easier for students to understand the learning provided. However, if they do not utilize media in the learning process, students will become less active in learning activities because the material presented is less attractive. This research aims to analyze the effect of using the Pop-Up Book of Geometry learning media on class students' understanding of building space. A quantitative approach with quasi-experimental methods was used in this research. The population was all class IV ICC Pahang students, totaling 18. The data analysis technique uses the related sample t-test to test the hypothesis. The analysis of learning completeness showed an average pretest score of 43.61 and a posttest of 77.78. This research showed that based on the hypothesis test results, it was found that Pop Up Book learning media influenced the learning outcomes of class IV students. It was concluded that Pop Up Book learning media can improve the learning outcomes of fourth-grade elementary school students.